Implementasi Qawaid Fiqih dalam Transaksi Ekonomi di Lembaga Keuangan Syariah - Sofyan, Abdul Rahman; Siregar, Meri Roito; Nasution, Laisa Asri; Dalimunthe, Mawar Rasimah Br. (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study discusses the implementation of Qawaid Fiqh in Islamic financial institution contract products in Indonesia. Qawaid Fiqh, which is the basic principles of Islamic law, plays a role in ensuring that economic transactions carried out by Islamic financial institutions are in accordance with Islamic principles. This study uses a descriptive analytical approach with a literature review that aims to understand how principles such as al-ashlu fil mu’amalat al-ibahah, la dharar wa la dhir?r, al-umuru bi maqasidiha, al-yaqin la yazulu bisyakk, and al-masyaqqah tajlibu at-taysir are applied in contract products such as murabahah, mudharabah, musyarakah, and takaful. The results of the study indicate that the application of Qawaid Fiqh in these contracts has been carried out in accordance with Islamic principles, but there are still challenges in its implementation, especially in terms of fairness, transparency, and avoidance of practices that are detrimental to certain parties. This study concludes that while Islamic financial institutions in Indonesia have implemented these principles, there is still a need to strengthen supervision and understanding of sharia among industry players to ensure more consistent and comprehensive implementation.